2022
DOI: 10.3390/molecules27030832
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Risk Assessment of Polybrominated Diphenyl Ethers in Surface Water and Sediment of Nahoon River Estuary, South Africa

Abstract: The concentrations, potential sources, and compositional profile of PBDEs in the surface water and sediment of Nahoon Estuary, East London, South Africa, were investigated with solid-phase extraction and ultra-sonication, respectively, followed by gas-chromatography-electron capture detection. The seasonal range of the contaminants’ concentrations in water and sediment samples in spring season were ∑PBDE 329 ± 48.3 ng/L (25.32–785 ng/L) and ∑PBDE 4.19 ± 0.35 ng/g dw (1.91–6.57 ng/g), but ∑PBDE 62.1 ± 1.50 ng/L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In two sampling sites in the Eastern Cape, the concentration of ∑PBDEs detected in water samples from Sundays Estuary ranged from 2.5 to 39.1 ng/L and Swartkops estuary ranged from 2.5 to 168.8 ng/L [ 43 ]. Ohoro et al [ 44 ] found a range of ∑PBDEs 30.1–785 ng/L in an estuary in East London, South Africa with different seasonal concentrations detected.…”
Section: Contaminants Currently Featured In the Cec Knowledge Hubmentioning
confidence: 99%
“…In two sampling sites in the Eastern Cape, the concentration of ∑PBDEs detected in water samples from Sundays Estuary ranged from 2.5 to 39.1 ng/L and Swartkops estuary ranged from 2.5 to 168.8 ng/L [ 43 ]. Ohoro et al [ 44 ] found a range of ∑PBDEs 30.1–785 ng/L in an estuary in East London, South Africa with different seasonal concentrations detected.…”
Section: Contaminants Currently Featured In the Cec Knowledge Hubmentioning
confidence: 99%